2017
DOI: 10.1038/s41598-017-08392-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-induced release of small extracellular vesicles (exosomes) with surface-associated DNA

Abstract: Recently, biological roles of extracellular vesicles (which include among others exosomes, microvesicles and apoptotic bodies) have attracted substantial attention in various fields of biomedicine. Here we investigated the impact of sustained exposure of cells to the fluoroquinolone antibiotic ciprofloxacin on the released extracellular vesicles. Ciprofloxacin is widely used in humans against bacterial infections as well as in cell cultures against Mycoplasma contamination. However, ciprofloxacin is an inducer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 67 publications
(92 reference statements)
6
115
0
Order By: Relevance
“…All culture medium composition and preparation details should be provided in methods. This should be customary for cell culture studies, and is doubly important here since supplements like glucose [38][39][40], antibiotics [41], and growth factors [42] can affect EV production and/or composition. Of special note are medium components that are likely to contain EVs, such as serum.…”
Section: Cell Culture Conditioned Mediamentioning
confidence: 99%
“…All culture medium composition and preparation details should be provided in methods. This should be customary for cell culture studies, and is doubly important here since supplements like glucose [38][39][40], antibiotics [41], and growth factors [42] can affect EV production and/or composition. Of special note are medium components that are likely to contain EVs, such as serum.…”
Section: Cell Culture Conditioned Mediamentioning
confidence: 99%
“…Multi-vesicular body (MVB)-derived extracellular vesicles (EVs) are constantly secreted into the extracellular space. These nanoparticles called exosomes are key to maintain homeostasis of their releasing (originating) cells [169][170][171][172]. They facilitate specific cell-cell interactions and stimulate several signaling pathways in their target cells, including cancer cells [173].…”
Section: Exosomesmentioning
confidence: 99%
“…EV-associated DNA may be single-stranded DNA, mitochondrial DNA, or double-stranded DNA 39,41,42 . The DNA content associated with EVs (termed EV-DNA) may be transported within the lumen of EVs 39,40 ; however, recent studies have shown that, depending on the biological context, EV-DNA can also be found attached to the outer surface of EVs [43][44][45][46] .…”
Section: Ev Genomicsmentioning
confidence: 99%